2008
DOI: 10.1002/ijc.23205
|View full text |Cite
|
Sign up to set email alerts
|

The impact of tobacco smoking and alcohol drinking on survival of patients with non‐Hodgkin lymphoma

Abstract: Tobacco smoking and alcohol consumption have not been clearly related to the risk of non-Hodgkin lymphoma (NHL), and the impact of these two factors on survival of NHL patients has received little attention. Cases were 268 subjects with incident histologically-confirmed NHL, admitted as inpatients to the Division of Medical Oncology, between 1983 and 2002. These individuals were enrolled as cases in case-control studies conducted at the same institution over the same period. For all patients clinical (histolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 30 publications
3
27
2
Order By: Relevance
“…Survival showed little difference by ethnicity except for Japanese Americans with CLL/SLL. Our finding of worse overall survival associated with smoking prior to NHL diagnosis agrees with previous reports (10, 27, 28) possibly due to creating a microenvironment that promotes tumor growth.…”
Section: Discussionsupporting
confidence: 92%
“…Survival showed little difference by ethnicity except for Japanese Americans with CLL/SLL. Our finding of worse overall survival associated with smoking prior to NHL diagnosis agrees with previous reports (10, 27, 28) possibly due to creating a microenvironment that promotes tumor growth.…”
Section: Discussionsupporting
confidence: 92%
“…The results were different in an Italian study, in which tobacco intake was shown to be positively correlated to NHL (Talamini et al, 2005). Other studies of NHLs comparing never-smokers and never-alcohol drinkers with ever-smokers and everalcohol drinkers demonstrated that tobacco and alcohol use was correlated with a poorer survival rate (Talamini et al, 2008;Geyer et al, 2010). In our study population, neither smoking nor alcohol drinking was found to be associated with DLBCL.…”
Section: Discussioncontrasting
confidence: 99%
“…When analyzed by subtype, the association was mainly observed for FL. Two subsequent studies also demonstrated the link between cigarette smoking and NHL survival [49,50]. However, one study observed a strong link with CLL/SLL and the other study with FL.…”
Section: Prognosismentioning
confidence: 95%